ANALISIS PERKEMBANGAN PEMIKIRAN FUNGSI DAN PERAN EKONOMI ISLAM DALAM MENGATASI KRISIS KEUANGAN GLOBAL - Lasimun Lasimun (JURNAL LENTERA BISNIS, 2012)
Mistake of looking at economic problems are causing errors in solving economic problems. Regard the capitalist economic system economic problems arise because of the scarcity of sources, while human needs are unlimited. Then the economic system provides a way out by way of how humans can increase production as much as possible to meet the needs that he is not limited. In this way the macro level is applied to the pursuit of economic growth as high. Of course the issue of whether the needs of each individual, especially their basic needs are met or not, is not considered a capitalist economic system. But that note is the owner of the capital so that they can improve and expand the production scale.Application of the Islamic economic system is an integral part of the application of Islamic law so that the Islamic economic system is the part that is not liberated by other shariah-Islamic law. Application of Islamic law in the economy is an obligation as the duty of every Muslim to perform the prayer, fasting, zakat and hajj. Thus inappropriate for us to ignore the economic activities of Islamic law to take, carry out and glorify other economic system based kufr law.Logical consequence of the implementation efforts of Islamic economic system is the state or daulah should apply Islamic law as a whole, including the country's system of Khilafah Islamiyah daulah. So in applying Islamic economic system have also been conducted simultaneously attempt to form and establish the Khilafah Islamiyah daulah.Any Muslim who believes in the truth of the Islamic faith, a duty for everyone to be bound by the laws of Personality (Islamic Shari'ah) when committed by only by the standards of halal and haram that have been outlined by Allah SWT. The point we are all obliged to carry out all the commands of Allah (lawful act) and stay away from all his ban (unlawful)